Analisis Pembelajaran Bahasa Arab Berbasis Konstruktivisme di MAN 1 Pamekasan - Nurlaila Nurlaila; Muassomah Muassomah (Taqdir, 2020)
Arabic Learning is a subject that is rarely interested by students so they find difficult to understand it. Therefore, the teacher must use the right approach in learning. This study aims to analyze and describe the process of Arabic learning based on the constructivism approach and the inhibiting factors of this learning process. To achieve these objectives, researcher use a qualitative approach with a descriptive type. To analyze the data obtained, researcher use interactive analysis. The results showed that the constructivist learning model applied in the process Arabic learning at MAN 1 Pamekasan is the Learning Cycle Constructivism Model which consists of three stages, namely discourse, concept recognition, and application of concepts. Learning Arabic at MAN 1 Pamekasan using the constructivism approach has not been running optimally. This is evidenced by the lack of student activity in learning activities, because several factors, it is the difference in the characteristics of each student, the limited time to deliver learning material, the lack of student interest in Arabic learning, the educational background of students before entering MAN 1 Pamekasan where, the number of students in each class was uneven, There are many mistakes in the worksheet (LKS), and the lack of learning tools and facilities.